Digitalizing Village Office Administration: The Role of Google Workspace in Improving Work Effectiveness - Zainul Arifin; Guruh Wijaya; Nur Qodariyah Fitriyah; Henny Wahyu Sulistyo; Dudi Irawan (Journal Of Humanities Community Empowerment, 2026)
Digital transformation in public administration has become an essential requirement to improve work effectiveness and the quality of public services, including at the village government level. One practical approach to support this transformation is the utilization of cloud-based collaboration platforms such as Google Workspace. However, the implementation of such technology in village offices still faces several challenges, particularly limited digital literacy among village officials and the suboptimal use of digital productivity tools for administrative tasks. Therefore, this community service activity aims to enhance the knowledge and skills of village officials in utilizing Google Workspace as a supporting tool for administrative management and public services. This community service program was conducted over two days at the village office and involved 13 village officials as participants. The service team consisted of five lecturers from the fields of Informatics Engineering and Information Systems. The implementation method included preparation, training, hands-on assistance, and evaluation stages. The training materials covered an introduction to cloud computing concepts, the use of Google Drive for document management, the utilization of Google Docs and Google Sheets for preparing official documents and data processing, as well as the use of Google Forms to support village administrative services. The results of the activity indicate a significant improvement in participants’ understanding and skills in using Google Workspace. Village officials were able to manage documents in a centralized cloud-based system, collaborate online in real time, and begin adopting more efficient and integrated digital administrative practices. This activity contributes positively to encouraging the digitalization of village administration and demonstrates the potential of technology-based community service programs to support sustainable improvements in local government performance.